Alexithymia, suicide ideation, affective temperaments and homocysteine levels in drug naïve patients with post-traumatic stress disorder: an exploratory study in the everyday 'real world' clinical practice. (2nd January 2020) - De Berardis, Domenico; Vellante, Federica; Fornaro, Michele; Anastasia, Annalisa; Olivieri, Luigi; Rapini, Gabriella; Serroni, Nicola; Orsolini, Laura; Valchera, Alessandro; Carano, Alessandro; Tomasetti, Carmine; Varasano, Paola Annunziata; et al.
Abstract: Objective: The present exploratory study aimed to investigate relationships between alexithymia, suicide ideation, affective temperaments and homocysteine levels among drug-naïve adult outpatients with Post-Traumatic Stress Disorder (PTSD) in an everyday 'real world' clinical setting. Method: Sixty-four adult outpatients with PTSD were evaluated using the Davidson Trauma Scale (DTS), the Toronto Alexithymia Scale (TAS–20), the Scale of Suicide Ideation (SSI), the Temperament Evaluation of the Memphis, Pisa, Paris and San Diego-Autoquestionnaire. As well, homocysteine levels were measured. Results: Alexithymic subjects showed higher values on all scales but not homocysteine levels. Partial correlations showed that almost all studied variables were correlated with each other, except homocysteine levels. Regression analysis showed that higher disorder severity as measured by DTS and TAS-20 'Difficulty in Identifying Feelings' dimension was associated with higher SSI scores. Conclusions: In conclusion, alexithymic PTSD outpatients may be characterised by higher disorder severity and difficulty in identifying feelings that may be linked to increased suicide ideation, regardless of affective temperaments or homocysteine levels. Homocysteine levels were not related to any studied variable. However, study limitations are discussed and must be considered. Keypoints: Patients with alexithymia showed increased PTSD severity, a higher score on TEMPS-A subscales, and more severe suicide ideation. The Difficulty in Identifying Feelings (DIF) dimension of TAS-20 was associated with suicide ideation in patients with PTSD. Homocysteine did not correlate with any studied variables. This study was exploratory and cross-sectional: further larger and prospective studies are needed.